Self-Inflicted Trauma Secondary to Local Anaesthesia in Children. (30th January 2017) - Vempaty, Srikrishna; Robbins, James
Abstract : Long acting local anaesthetics and inferior alveolar nerve block in children can cause loss of sensation and proprioception in a large area supplied by that particular nerve. Similar to the maxilla in mandible also, adequate level of anaesthesia can be achieved in the desired site of treatment by using a short acting local anaesthetic. Early return of normal sensory feedback after using short acting anaesthetics can be helpful in preventing self-harm.